Analysis of the Success of Knowledge Management Implementation in the Customer Relationship Management Framework at PT. Telkom Indonesia - Afwa Mufti Salis; Fauzi Hisbullah; Alif Noorachmad Muttaqin; Fahdi Saidi Lubis (Acceleration, Quantum, Information Technology and Algorithm Journal, 2025)
Implementation of knowledge management has emerged as an essential strategic move for organizations aiming to improve their performance and competitiveness during the digital age. Among the biggest telecommunication firms operating in Indonesia is PT Telkom Indonesia, which has implemented a range of knowledge management activities to support their business and customer relationship operations. This paper aims to explore the critical factors expected to impact the successful installation of knowledge management within the context of the CRM process in PT Telkom Indonesia. A descriptive approach involving the literature study was employed to evaluate the range of issues pertinent to the knowledge management process from the technology and human perspective. It has been found that the critical factors for the successful installation of knowledge management include the adaptation and commitment of the leadership and staff participation and involvement. Moreover, the integration of knowledge management operations and the process of CRM helps generate greater knowledge for the purpose of supporting customers-focused decisions. This study's findings provide valuable information to firms operating within the telecommunication sector to understand how to design an effective knowledge strategy by integrating the CRM strategy for gaining the intended competitive advantage.